The mechanisms of nickel toxicity in aquatic environments: An adverse outcome pathway analysis. (22nd January 2017) - Brix, Kevin V.; Schlekat, Christian E.; Garman, Emily R.
Abstract: Current ecological risk assessment and water quality regulations for nickel (Ni) use mechanistically based, predictive tools such as biotic ligand models (BLMs). However, despite many detailed studies, the precise mechanism(s) of Ni toxicity to aquatic organisms remains elusive. This uncertainty in the mechanism(s) of action for Ni has led to concern over the use of tools like the BLM in some regulatory settings. To address this knowledge gap, the authors used an adverse outcome pathway (AOP) analysis, the first AOP for a metal, to identify multiple potential mechanisms of Ni toxicity and their interactions with freshwater aquatic organisms. The analysis considered potential mechanisms of action based on data from a wide range of organisms in aquatic and terrestrial environments on the premise that molecular initiating events for an essential metal would potentially be conserved across taxa. Through this analysis the authors identified 5 potential molecular initiating events by which Ni may exert toxicity on aquatic organisms: disruption of Ca 2+ homeostasis, disruption of Mg 2+ homeostasis, disruption of Fe 2+/3+ homeostasis, reactive oxygen species–induced oxidative damage, and an allergic‐type response of respiratory epithelia. At the organ level of biological organization, these 5 potential molecular initiating events collapse into 3 potential pathways: reduced Ca 2+ availability to support formation of exoskeleton, shell, and bone for growth; impaired respiration; and cytotoxicity and tumor formation. At the level of the whole organism, the organ‐level responses contribute to potential reductions in growth and reproduction and/or alterations in energy metabolism, with several potential feedback loops between each of the pathways. Overall, the present AOP analysis provides a robust framework for future directed studies on the mechanisms of Ni toxicity and for developing AOPs for other metals. Environ Toxicol Chem 2017;36:1128–1137. © 2016 SETAC